ATLAS2030 Pediatric Gait Exoskeleton: Changes on Range of Motion, Strength and Spasticity in Children With Cerebral Palsy. A Case Series Study - Delgado, Elena; Cumplido, Carlos; Ramos, Jaime; Garcés, Elena; Puyuelo, Gonzalo; Plaza, Alberto; Hernández, Mar; Gutiérrez, Alba; Taverner, Thomas; Destarac, Marie André; Martínez, Mercedes; García, Elena (Frontiers in Pediatrics, 2021)
Background: Cerebral Palsy (CP), the most common motor disability in childhood, affects individual’s motor skills, movement and posture. This results in limited activity and a low social participation. Rehabilitation focused on Robot-Assisted Gait Training (RAGT) has shown to improve their mobility and it is increasingly being used in pediatric neurorehabilitation to complement conventional physical therapy. Purpose: To study changes in relation to musculoskeletal variables such as range of motion, strength and spasticity in children with CP after using the ATLAS2030 gait exoskeleton. Methods and participants: Three children (mean age 8.0 ± 2.0) received RAGT with ATLAS 2030 for one month. All modes of use of the exoskeleton were tested: forward and backward walking, gait in passive and active modes. Results: The average time of use was 54.7 ± 10.4 minutes. The strength of all muscle groups was increased after the 10 sessions for the participants assessed and the flessums in the sagittal plane (hip and knee extension and ankle dorsiflexion) decreased after the use of the exoskeleton compared to the initial state. Conclusion: The range of motion, spasticity and strength were improved after RAGT with ATLAS2030 exoskeleton in children with cerebral palsy. However, further studies with larger samples should be carried out to confirm this affirmation.